Neutrophil Cyto‐Pharmaceuticals Suppressing Tumor Metastasis via Inhibiting Hypoxia‐Inducible Factor‐1α in Circulating Breast Cancer Cells. Issue 3 (7th December 2021) - Zhang, Ying; Wang, Cong; Li, Weishuo; Tian, Wei; Tang, Chunming; Xue, Lingjing; Lin, Ziming; Liu, Guilai; Liu, Dongfei; Zhou, Ying; Wang, Qianqian; Wang, Xu; et al.
Abstract: Circulating tumor cells (CTCs) are reported as the precursor of tumor metastases, implying that stifling CTCs would be beneficial for metastasis prevention. However, challenges remain for the application of therapies that aim at CTCs due to lack of effective CTC‐targeting strategy and sensitive therapeutic agents. Herein, a general CTC‐intervention strategy based on neutrophil cyto‐pharmaceuticals is proposed for suppressing CTC colonization and metastasis formation. Breast cancer 4T1 cells are infused as the mimic CTCs, and 4T1 cells trapped are first elucidated in neutrophil extracellular traps (NETs) expressing high levels of hypoxia‐inducible factor‐1 α (HIF‐1 α ) due to NET formation and thus promoting tumor cell colonization through enhanced migration, invasion and stemness. After verifying HIF‐1 α as a potential target for metastasis prevention, living neutrophil cyto‐pharmaceuticals (CytPNEs) loaded with HIF‐1 α inhibitor are fabricated to therapeutically inhibit HIF‐1 α . It is demonstrated that CytPNEs can specially convey the HIF‐1 α inhibitor to 4T1 cells according to the inflammatory chemotaxis of neutrophils and down‐regulate HIF‐1 α, thereby inhibiting metastasis and prolonging the median survival of mice bearing breast cancer lung metastasis. The research offers a new perspective for understanding the mechanism of CTC colonization, and puts forward the strategy of targeted intervention of CTCs as a meaningful treatment for tumor metastasis. Abstract : Circulating breast cancer cells (CTCs)‐interrupting neutrophil cyto‐pharmaceuticals (CytPNEs) for inhibition of tumor metastasis is proposed. CytPNEs can be effectively recruited to the CTCs trapped in the NETs (CTC‐NET clusters) due to the inflammatory chemotaxis, followed by down‐regulating the HIF‐1 α level in CTCs, and finally reduce the formation of tumor metastasis through suppressing CTC colonization and development.